Notes on the identity of Phalaena Attacus cassandra Cramer, [1779] (Lepidoptera: Saturniidae, Arsenurinae) - V. O. Becker (SHILAP)
The identity of Phalaena Attacus cassandra Cramer, [1779] is established, based on a female reared from a caterpillar that matched the description and illustration by STOLL (1790), raising the following questions: Are Attacus armida and Attacus cassandra really the same species, or two different species, as supposed by CRAMER (1771 [1779]), when described the adults, and Stoll, when he described the caterpillars? If they are the same, are the caterpillars polymorphic? Illustrations of the larvae and adult provide evidence that support these questions.